Assessing patients' beliefs about cardiac rehabilitation as a basis for predicting attendance after acute myocardial infarction. Issue 1 (11th August 2006) - Cooper, A F; Weinman, J; Hankins, M; Jackson, G; Horne, R
Abstract : Background: Some sociodemographic and psychological variables such as patients' belief about illness are associated with attendance at cardiac rehabilitation. Exploration of patients' beliefs about treatment regarding cardiac rehabilitation has been limited to qualitative studies; their role in relation to attendance at cardiac rehabilitation after acute myocardial infarction (AMI) remains speculative. Objectives: To develop a valid and reliable measure of patients' beliefs regarding cardiac rehabilitation and to ascertain the relationship between such beliefs and attendance. Design: A prospective questionnaire-based study. Setting: Coronary care unit of a London teaching hospital. Patients: 130 patients with AMI; 104 (83%) men; mean age 58.4 (standard deviation (SD) 10.7) years. Interventions: Patients completed a 26-item questionnaire consisting of statements pertaining to beliefs about cardiac rehabilitation. Main outcome measures: Cardiac rehabilitation attendance; beliefs of patients about cardiac rehabilitation. Results: Four subscales pertaining to patients' beliefs about cardiac rehabilitation were produced, accounting for 65.3% of the attendance variance: perceived necessity of cardiac rehabilitation (α = 0.71), concerns about exercise (α = 0.79), practical barriers (α = 0.70) and perceived personal suitability (α = 0.74). Patients who attended were more likely to believe that cardiac rehabilitation was necessary and to understand its role compared with non-attenders (17.7 (SD 2.7) v 16.9 (SD 3.0), p = 0.029). Patients who thought cardiac rehabilitation was suitable for a younger, more active person were less likely to attend (5.6 (SD 1.9) v 4.6 (SD 1.7), p = 0.007). Patients who expressed concerns about exercise or who reported practical barriers to attendance were less likely to attend, although these did not reach statistical significance. Conclusion: Beliefs about cardiac rehabilitation can be quantified and differ between attenders and non-attenders of cardiac rehabilitation.